2021
DOI: 10.1097/qai.0000000000002808
|View full text |Cite
|
Sign up to set email alerts
|

Uptake, Retention, and Adherence to Pre-exposure Prophylaxis (PrEP) in TRIUMPH: A Peer-Led PrEP Demonstration Project for Transgender Communities in Oakland and Sacramento, California

Abstract: Background:TRIUMPH (Trans Research–Informed communities United in Mobilization for the Prevention of HIV) was a community-led, transgender-specific pre-exposure prophylaxis (PrEP) demonstration project at 2 community-based clinical sites in California. TRIUMPH used peer health education, community mobilization, and clinical integration of PrEP with hormone therapy to promote PrEP knowledge and acceptability. The goal of this study was to evaluate PrEP uptake, retention, and adherence among TRIUMPH participants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 39 publications
0
27
0
1
Order By: Relevance
“…This finding is consistent with studies that have found that receiving quality, affirming health services in a welcoming and trans-friendly environment was associated with increased engagement in sexual health services 42 and where trans clients can connect and derive support from one another as well as from their providers. 64,65 Gender affirmation 43 and healthcare empowerment 66 have been shown to moderate the deleterious impact that trans-related discrimination has on rates of viral suppression among Black and Latinx TGW with HIV. 67 Guidelines for gender-affirming care of trans and non-binary people include ensuring a safe and welcoming environment by utilizing a patient's gender identity, and taking a gender-affirming approach for any physical exams.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is consistent with studies that have found that receiving quality, affirming health services in a welcoming and trans-friendly environment was associated with increased engagement in sexual health services 42 and where trans clients can connect and derive support from one another as well as from their providers. 64,65 Gender affirmation 43 and healthcare empowerment 66 have been shown to moderate the deleterious impact that trans-related discrimination has on rates of viral suppression among Black and Latinx TGW with HIV. 67 Guidelines for gender-affirming care of trans and non-binary people include ensuring a safe and welcoming environment by utilizing a patient's gender identity, and taking a gender-affirming approach for any physical exams.…”
Section: Discussionmentioning
confidence: 99%
“…Future PrEP interventions for TGNB should consider adding behavioral content that bolsters coping skills and strengthens social support for PrEP as these appear to be promising targets for increasing uptake and persistence on PrEP among TGNB persons. However, it is important to note that these interventions must be delivered within gender-affirming healthcare and prevention services settings in order to be maximally effective at bolstering PrEP engagement among TGNB persons [4,88,89].…”
Section: Discussionmentioning
confidence: 99%
“…Violence against transgender and non-binary (TGNB) persons (persons whose gender identity differs from the sex they were assigned at birth) has deleterious effects on the health and wellbeing of TGNB persons including increasing HIV risk [1][2][3]. While little is currently known about the impact of gender-based violence (GBV) on engagement in HIV prevention behaviors such as pre-exposure prophylaxis (PrEP) among TGNB persons, a recent study found PrEP use 1 3 to be negatively associated with recent experience of violence generally [4]. TGNB persons experience violence on the basis of their gender expression, gender identity, gender nonconformity, and/or their perceived sexual orientation [1].…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, gender affirmation, the process of recognizing and supporting a TNB person's gender, is associated with engagement in HIV care and viral suppression [16] and uptake of biomedical HIV prevention [12,17].…”
Section: Introductionmentioning
confidence: 99%
“…Quantitative studies have shown negative associations between anti‐trans stigma and HIV care access [ 14 ], whereas qualitative studies have identified how intersecting anti‐trans and HIV stigma limit trans women's access to HIV prevention/care [ 15 ]. Conversely, gender affirmation, the process of recognizing and supporting a TNB person's gender, is associated with engagement in HIV care and viral suppression [ 16 ] and uptake of biomedical HIV prevention [ 12 , 17 ].…”
Section: Introductionmentioning
confidence: 99%